1999
DOI: 10.1038/sj.bmt.1701637
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cell contamination in mantle cell non-Hodgkin lymphoma: the case for purging?

Abstract: Summary:Intensification using peripheral blood stem cells collected after chemotherapy followed by growth factors is being increasingly investigated as an alternative to conventional chemotherapy for mantle cell non-Hodgkin lymphoma. We investigated 14 grades III-IV, t(11;14)-positive cases for contamination of PBSC collected after a polychemotherapy regimen followed by G-CSF. Patients were first treated with a polychemotherapy regimen. There were four CR, seven PR, two refractory and one early death. Seven pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…In contrast, the results in Figure 2 show that all 20 informative patients treated with R-HDS yielded very large amounts of CD34 ϩ cells, devoid of mantle cell contamination. Of note, this very high eradication rate was obtained in patients starting with an overt leukemic PB pattern in 57% of the cases and showing (as observed previously by Jacquy et al 25 ), a massive lymphoma-cell mobilization following the initial 3 courses of conventional chemotherapy. These results confirm and extend our original observation 15 that the combination of high-dose chemotherapy and rituximab represents a very effective in vivo purging method in this otherwise hard to purge disease.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, the results in Figure 2 show that all 20 informative patients treated with R-HDS yielded very large amounts of CD34 ϩ cells, devoid of mantle cell contamination. Of note, this very high eradication rate was obtained in patients starting with an overt leukemic PB pattern in 57% of the cases and showing (as observed previously by Jacquy et al 25 ), a massive lymphoma-cell mobilization following the initial 3 courses of conventional chemotherapy. These results confirm and extend our original observation 15 that the combination of high-dose chemotherapy and rituximab represents a very effective in vivo purging method in this otherwise hard to purge disease.…”
Section: Discussionsupporting
confidence: 52%
“…Of note, during the hematologic recovery following the standard-dose induction chemotherapy cycles, these patients showed a marked increase in the number of circulating lymphoma cells at a time when solid tumor masses were shrinking. This chemotherapy-elicited leukemization, already reported by Jacquy et al, 25 was no longer evident after subsequent high-dose chemotherapy cycles. Of the 28 study patients, there was 1 acute in-hospital treatmentrelated death from cardiac arrhythmia and 3 relapses at 9, 13, and 31 months.…”
Section: Response and Survivalmentioning
confidence: 50%
“…The issue of tumor cell contamination has not been studied in this trial but it is well known that tumor cells can be detected in peripheral blood stem cell grafts even in patients with no measurable disease (Jacquy et al 1999;Kruger et al 2001). Kruger and coworkers also demonstrated that the presence or absence of tumor cells in apheresis samples could not be safely predicted by the presence or absence of tumor cells in marrow or blood.…”
Section: Discussionmentioning
confidence: 95%
“…However, our results contribute to the discussion concerning the utility of graft purging in MCL patients. Recently published papers have demonstrated the resistance of MCL cells to both in vivo 10 and ex vivo purging 6 as well as negligible clinical benefit of the latter strategy. 7 Our limited data do not demonstrate the benefits of CD34 + cell selection and are thus in agreement with others testifying that, to date, there is no evidence that purging by any means could significantly influence disease-free survival.…”
mentioning
confidence: 99%